War on Terrorism & Kashmir issue - Shaheen Akhtar (Journal of Political Studies, 2007)
The dynamics of Kashmir conflict have undergone a drastic change since 9/11 due to dramatic changes wrought by US War on Terrorism in the region. The US focus on fighting terrorism, extremism and Islamic fundamentalism, most of the times all linked together has put tremendous pressure on Pakistan’s Kashmir policy. With the blurring of distinction between freedom struggle and terrorism, international community has become more intolerant to terrorism. Finding the moment opportune, New Delhi has stepped up the ante and questioned Pakistan’s sincerity and commitment to fight terrorism while “sponsoring cross-border terrorism” into Indian held Kashmir. Conversely, Islamabad walking on a tightrope has tried to maintain a distinction between freedom struggle and terrorism. The objective of the paper is to explore the relationship between War on Terror and Kashmir issue since 9/11. It analyses the relationship between War on Terror and Kashmir issue from three competing perspectives emanating from Islamabad, New Delhi and Washington. The Kashmiri perspective on War on Terrorism is also integrated in the analysis. The main argument is that although War on Terrorism has put pressure on the armed struggle in Kashmir, it has pushed political struggle to the forefront which provides an opportunity for serious negotiations on the Kashmir issue.